Changes of the Proteome and Acetylome during Transition into the Stationary Phase in the Organohalide-Respiring Dehalococcoides mccartyi Strain CBDB1 - Franziska Greiner-Haas; Martin von Bergen; Gary Sawers; Ute Lechner; Dominique Türkowsky (Microorganisms, 2021)
The strictly anaerobic bactGIerium Dehalococcoides mccartyi obligatorily depends on organohalide respiration for energy conservation and growth. The bacterium also plays an important role in bioremediation. Since there is no guarantee of a continuous supply of halogenated substrates in its natural environment, the question arises of how D. mccartyi maintains the synthesis and activity of dehalogenating enzymes under these conditions. Acetylation is a means by which energy-restricted microorganisms can modulate and maintain protein levels and their functionality. Here, we analyzed the proteome and Nε-lysine acetylome of D. mccartyi strain CBDB1 during growth with 1,2,3-trichlorobenzene as an electron acceptor. The high abundance of the membrane-localized organohalide respiration complex, consisting of the reductive dehalogenases CbrA and CbdbA80, the uptake hydrogenase HupLS, and the organohalide respiration-associated molybdoenzyme OmeA, was shown throughout growth. In addition, the number of acetylated proteins increased from 5% to 11% during the transition from the exponential to the stationary phase. Acetylation of the key proteins of central acetate metabolism and of CbrA, CbdbA80, and TatA, a component of the twin-arginine translocation machinery, suggests that acetylation might contribute to maintenance of the organohalide-respiring capacity of the bacterium during the stationary phase, thus providing a means of ensuring membrane protein integrity and a proton gradient.